PENERAPAN ANGGARAN BELANJA DENGAN PENDEKATAN KINERJA (PERFORMANCE BUDGET) PADA PENGELOLAAN KEUANGAN PROVINSI BALI - Ketut Ayuningsasi, Anak Agung (INPUT Jurnal Ekonomi dan Sosial, 2009)
Logical consequence of the implementation of regional autonomy causes changes in the regional financialmanagement. The changes, among others, are the needs for budgeting reform, that is, from the traditional budgetto performance budget. Performance budget very emphasizing at concept of value for money that is economic,efficiency, and effectiveness principle.This article aims to know the implementation of performance budget in Bali Province. It analized the allocationof regional expenditure after the implementation of performance budget. Before the application of budgeting withthe performance approach, the implementation of regional budgeting in the Bali Province shows lack of efficiencyin the use of budget. This is indicated by the higher routine expenditure compared with the expenditure fordevelopment with relatively high allocated miscellaneous expenditure. Through the implementation of performancebudget, hopefully the regional expenditure allocated for development is higher than routine consumption. It meansthat government concerned in public money, so they can accomplish their main function which is to improve public welfare.